Chapter 9 Starting with the End in Mind by Developing Diagnostics around User Needs - David Lim, Mark (Taylor & Francis, 2017)
As discussed in this chapter, the commercialization and adoption bottlenecks for these moderately complex diagnostics cannot be overcome by technological innovation alone, particularly in the highly regulated and payer-limited healthcare and public health markets. Diagnostics, unlike other clinical products, is not an intervention but a decision-aid that guides the use (or nonuse) of an intervention. It is important that the value proposition for any technology-centric innovation in diagnostics include a strong link to a gained efficiency in making a specific decision. Any assay developed without context to the system, users, decision points, and downstream interventions resembles one that is more targeted to the research community, rather than clinical care or public health.